Resection or ablation versus transarterial therapy for Child-Pugh A patients with a single small hepatocellular carcinoma. Issue 43 (29th October 2021) - Suh, Young Ju; Jin, Young-Joo; Jeong, Yujin; Shin, Woo Young; Lee, Jeong-min; Cho, Soongu; Yu, Jung Hwan; Lee, Jin-Woo
Abstract : Abstract: Data from a direct comparison of the long-term survival outcomes of surgical resection (SR) or radiofrequency ablation (RFA) versus transarterial therapy in Child-Turcotte-Pugh (CTP)-class A patients with a single small T1/T2 stage hepatocellular carcinoma (HCC) (⩽3 cm) are still lacking. This study retrospectively compared the therapeutic outcomes of these treatment types for CTP-A patients with a single small HCC. Using a nationwide Korean registry, we identified 2314 CTP-A patients with SR (n = 722), RFA (n = 731), or transarterial therapy (n = 861) for a single (⩽3 cm) T1/T2 stage HCC from 2008 to 2014. The posttreatment overall survival (OS) of transarterial therapy with either SR or RFA were compared using the Inverse Probability of treatment Weighting (IPW). The median follow-up period was 50 months (range 1–107 months). After IPW, the cumulative OS rates after SR or RFA were significantly higher than those after transarterial therapy in all subjects (all P values < .05). The OS rates after SR or RFA were better than those after transarterial therapy in patients with the hepatitis B or C virus (all P values < .05), and in patients aged <65 years (all P values < .05). The cumulative OSs between RFA and transarterial therapy were statistically comparable in patients with a 2 to 3 cm HCC and aged ≥65 years, respectively. For all subjects, the weighted Cox proportional hazards model using IPW provided the adjusted hazard ratios (95% confidence interval) for the OS after SR versus transarterial therapy and after RFA versus transarterial therapy of 0.42 (0.30–0.60) ( P  < .001) and 0.78 (0.61–0.99) ( P  = .044), respectively. In CTP-A patients with a single (⩽3 cm) T1/T2 HCC, SR or RFA provides a better OS than transarterial therapy, regardless of the HCC etiology (hepatitis B virus or hepatitis C virus), especially in patients with HCC of <2 cm and aged <65 years. Abstract : Supplemental Digital Content is available in the text